Hybridising signaling principle and nielsen’s design guidelines in a mobile application - Arifah Fasha Rosmani,; Ariffin Abdul Mutalib,; Siti Mahfuzah Sarif, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Learning via mobile phone is very common nowadays, whether at the primary or tertiary stage. The use of mobile phones is causing growing concern among the general public. Improving online education, primarily via this device, is also one of the government’s most pressing needs. Most current research on mobile learning applications pays little attention to multimedia principles, especially the Signalling principle, to improve user interaction. As a result, this project is undertaken to suggest better and more efficient mobile learning applications. The model is developed in collaboration with various stakeholders, including content experts, HCI experts, actual users, and a thorough literature review. Creating these mobile learning design guidelines is anticipated to lead to a more efficient and successful mobile learning style. According to the results of the experiments, implementing the hybridised guidelines resulted in a significant increase in Asmaul Husna Islamic knowledge among university students.